Portable non-contact surface roughness measuring device - Z. F. Z., Abidin; T., Jing Hung; M. Nafis, O. Z. (IOP Publishing, 2019)
This paper outlines a development of non-contact surface roughness measuring tool by using non-contact method. Major works involve development of the non-contact surface roughness measuring tool toward flat surface. Non-contact method was developed to prevent damage and scratch from the workpiece. In order to develop the tool, optical sensor is used as the input signal for microcontroller. Voltage signal received from optical signal is translated into surface roughness measurement value by using mathematical formula. C++ language programming is used as the code instruction for Arduino microcontroller. The results indicate that the developed tool is capable to measure surface roughness for flat surface metal with non-contact method.